Hematological findings of canine ehrlichiosis: A case study (Research, Society and Development, 2024)
Canine ehrlichiosis, caused by the bacteria Ehrlichia canis, is an infectious disease transmitted by ticks that affects dogs of all breeds, ages and sexes. Its symptoms can vary from mild to intense, and may even be asymptomatic. Diagnosis is crucial and can be made through clinical signs and hematological findings, with blood counts being an essential tool. This study investigated the hematological findings of ehrlichiosis in five cases of dogs diagnosed with the disease. Changes such as normocytic normochromic anemia, thrombocytopenia, leukocytosis and pancytopenia were observed, varying according to the stage of the disease. In severe cases, blood transfusions and fluid therapy were necessary for treatment. Discussion of the cases revealed the progression of the disease, from initial cases with subtle symptoms to severe cases with organ failure. Worsening ehrlichiosis has been associated with low platelet counts as the disease progresses, highlighting the importance of early diagnosis. It is concluded that canine ehrlichiosis represents a significant challenge for the health of dogs, and raising awareness among owners about the severity of the disease is essential. Prevention, through educational campaigns and early diagnosis through blood counts, is essential for effective treatment and a favorable prognosis for affected animals.